Encyclopedia of pharmaceutical technology : 2004 update supplement - Swarbrick, James, 1934-; Boylan, James C. (New York : Marcel Dekker, 2004)
This supplement to the Second Edition of the Encyclopedia of Pharmaceutical Technology heralds transformations and advances in the design, development, manufacture, testing, and regulation of pharmaceuticals-supplying over 40 expert-authored articles as well as nearly 1900 new references to groundbreaking research studies
v. 1. A-D (p. 1-1032) -- v. 2. E-Pat (p. 1033-2044) -- v. 3. Ped-Z (p. 2045-3032).
Includes bibliographical references and index.
Keywords: Pharmaceutical technology -- Encyclopedias; Technology, Pharmaceutical -- Encyclopedias -- English; Pharmaceutical Preparations -- Encyclopedias -- English